REPRESENTASI PEREMPUAN DALAM IKLAN SUSU JAHE SIDO MUNCUL VERSI SIDO SUSU - Dyah Ratmasanti, Ni Nyoman Irafani; Purnawan, Ni Luh Ramaswati; Pradipta, Ade Devia (E-Jurnal Medium; Vol 1 No 1 (2020): Jurnal Ilmu Komunikasi 2020, 2020)
ABSTRACT       Susu Jahe Sido Muncul Sido Susu version is an advertisement that illustrates how the mass media still uses sensuality and exploitation of women as a means to attract the attention of the audience. This ad contains information about the "Undian Berhadiah Sido Susu", where Cupi Cupita as the brand ambassador conveys that information. Submission of information is accompanied by Cupi Cupita’s scene that moves the breast and hips This study used the analysis of Charles Peirce's semiotics by analyzing the objects contained in the sign shown by Cupi Cupita who represent women in this advertisement. Some supporting attributes such as the use of tight red clothing that contains sexual meanings, and seductive body language are added to further strengthen the impression of sensuality in this ad. The sensuality of women also directs the stereotype of women as sexual objects .   Keywords : Exploitation of Women, Representation of Women, Semiotics, Advertisement